Contemporary Sociological Theory: An Integrated Multi-Level Approach - Johnson, Doyle Paul (Springer, 2017)
This volume is designed as a basic text for upper level and graduate courses in contemporary sociological theory. Most sociology programs require their majors to take at least one course in sociological theory, sometimes two. A typical breakdown is between classical and contemporary theory. Theory is perhaps one of the bro- est areas of sociological inquiry and serves as a foundation or framework for more specialized study in specific substantive areas of the field. In addition, the study of sociological theory can readily be related to various aspects of other social science disciplines as well. From the very beginning sociology has been characterized by alternative theoretical perspectives. Classical theory includes the European founding figures of the dis- pline whose works were produced during the later half of the nineteenth century and the first couple of decades of the twentieth century plus early American th- rists. For most of the second half of the twentieth century, a fairly high consensus has developed among American sociologists regarding these major founders, p- ticularly with regard to the works of Durkheim and Weber in analyzing the overall society and of Simmel in analyzing social interaction processes. Since the late 1960s and early 1970s the influence of Marx has also been recognized. Recent decades have also witnessed an increased emphasis on the important contributions of several pioneering feminist perspectives in the early years of sociology.